Attitudes towards disclosing a mental illness among German soldiers and their comrades. (December 2017) - Rüsch, Nicolas; Rose, Carolyn; Holzhausen, Fabian; Mulfinger, Nadine; Krumm, Silvia; Corrigan, Patrick W.; Willmund, Gerd-Dieter; Zimmermann, Peter
Abstract: Many soldiers with mental illness (SWMIs) struggle with the decision whether to disclose their condition in or outside the military. This study therefore explored views on (self-)labeling as 'mentally ill', experiences of discrimination and coping, risks and benefits of (non-)disclosure, service use, disclosure decisions and consequences of disclosing. Active-duty SWMIs as well as soldiers without mental illness (commanding officers; enlisted ranks) and military social workers participated in focus groups. Transcripts were analyzed using qualitative content analysis. SWMIs perceived negative stereotypes about their group (weakness, incompetence, blame, malingering) and saw stigma as a barrier to help-seeking. Being labeled 'mentally ill' was seen as harmful for one's career. Self-labeling led to poor self-esteem, greater need for help and feelings of weakness. Many SWMIs had experienced discrimination, such as gossip or inappropriate comments. Social isolation was a disadvantage of secrecy. Most SWMIs preferred selective disclosure and many did not disclose to their family. Military staff without mental illness expressed partly different views and described organizational challenges posed by SWMIs. Our findings suggest that disclosure decisions are personal and difficult and that stigma remains a barrier to re-integration and recovery of SWMIs in the military. Implications for interventions to support SWMIs are discussed. Highlights: Common negative stereotypes about soldiers with mental illness include weakness, incompetence, blame and malingering. Disclosing a mental illness can lead to gossip, discrimination as well as negative career consequences. Non-disclosure is often a barrier to mental health service use and is associated with social isolation. Disclosure decisions are often difficult; selective disclosure is a common strategy and also recommended by military staff without mental illness.